Effect of detoxification methods on the proximate composition of kayos (Dioscorea hispida Dennst) - Abalunan, Juvy Ganza (2005.)
Kayos has been consideredas an alternative food during shortage of staple crops in many upland communities.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Detoxification; Proximate composition; Kayos; Dioscorea hispida Dennst